Investigating Apoptozole as a Chemical Probe for HSP70 Inhibition. - Lindsay E Evans; Matthew D Cheeseman; Norhakim Yahya; Keith Jones (PLoS ONE)
The use of chemical tools to validate clinical targets has gained in popularity over recent years and the importance of understanding the activity, selectivity and mechanism of action of these compounds is well recognized. Dysregulation of the HSP70 protein family has been linked to multiple cancer types and drug resistance, highlighting their importance as popular targets for anti-cancer drug development. Apoptozole is a recently identified small molecule, which has been reported to possess strong affinity for the HSP70 isoforms HSP72 and HSC70. We investigated apoptozole as a potential chemical tool for HSP70 inhibition. Unfortunately, using both biochemical and biophysical techniques, we were unable to find any experimental evidence that apoptozole binds to HSP70 in a specific and developable way. Instead, we provide experimental evidence that apoptozole forms aggregates under aqueous conditions that could interact with HSP70 proteins in a non-specific manner.